Prevalence of obesity among Bangladeshi pregnant women at their first trimester of pregnancy - Shatabdi Goon (University Library System, University of Pittsburgh, 2013)
BACKGROUND: Paradoxically, the escalating global epidemic of maternal obesity coexists with malnutrion in many areas of Bangladesh. This proves a major challenge to obstetric practice from preconception to postpartum due to related comorbid conditions including: maternal death or severe morbidity, gestational diabetes and hypertension, increased risk of early and recurrent miscarriage, pre-eclampsia, thromboembolism, post-caesarean wound infection, postpartum haemorrhage, and low breastfeeding rates. A dramatic increase in birth defects and other pregnancy-induced disorders related to maternal obesity has added millions of dollars to health care costs leading great economical loss to the country. OBJECTIVE: The study was designed to determine the prevalence of obesity among Bangladeshi pregnant women in their 1st trimester of pregnancy. STUDY DESIGN: 426 pregnant women presenting to the antenatal care until of Azimpur maternity hospital of Dhaka, Bangladesh were randomly selected for this cross sectional study to determine their weight status using body mass index (BMI, kg/m2). RESULT: 90 (21.2%) pregnant women were reported as obese with pregnancy BMI of >30 kg/m2. 171 (40.1%) and140 (32.8%) pregnant women were reported as overweight and healthy with pregnancy BMI of 25-29.9 kg/m2 and 18.5-24.9 kg/m2, respectively.Statistical analysis revealed obesity and overweight status were found to be significantly associated with age; women aged 31 or above were more likely to be obese (OR=2.5; 95% CI 1.53-3.96) and overweight (OR=3.3; 95% CI 2.15-4.99). CONCLUSION: This study provides evidence of increasing trends in obesity among Bangladeshi pregnant women, which poses possible health risks both for mother and child. The findings of this study may act as baseline data for monitoring the effectiveness of national programs for the prevention and control of maternal obesity.